Assessing and addressing domestic abuse by Ex-armed service personnel - Madoc-Jones, Iolo (Probation journal, 2018)
In the context that separate peer-led services are increasingly being developed to meet the needs of Ex-armed service personnel (Ex-asp) in the criminal justice system, we explore whether such services should also be developed to address any tendencies towards domestic abuse. Based on interviews with 12 imprisoned Ex-asp and 10 service-affiliated informants working with them, we found domestic abuse is not always recognized as a potential problem for Ex-asp. Nonetheless, respondents suggested that interventions to address the potential for domestic abuse by some Ex-asp would be useful and legitimate if they are provided by those with service affiliations. Considering our findings, however, we strike a note of caution about separate and peer-led approaches becoming the default option for working with Ex-asp in the criminal justice system. We suggest the gendered nature of military culture may be associated with concerns about the implications of re-engaging Ex-asp with their military identities. Moreover, being steeped in military culture, we suggest that without training some service-affiliated staff may be unsighted on important aspects of the role gender expectancies play in domestic abuse and poorly placed to respond appropriately to this type of offending.